Partial ampullary endoscopic mucosal resection in patients with difficult biliary cannulation: a prospective cohort study - Tokmak, Salih; Cetin, Mehmet Fuat; Sirin, Abdullatif; Konur, Sevki; Torun, Serkan (Endoscopy, 2025)
The rescue techniques available for cannulation failure are few in number and have severe limitations. We recently described partial ampullary endoscopic mucosal resection (PA-EMR) as a novel technique for difficult biliary cannulation. We aimed to demonstrate the efficacy and safety of PA-EMR for patients with difficult biliary cannulation in a larger cohort.We conducted a prospective cohort study at our tertiary care referral hospital. We recorded demographic factors, procedure-related characteristics, and adverse event rates in patients with difficult biliary cannulation who underwent PA-EMR.Between June 2021 and June 2022, we performed 1073 consecutive endoscopic retrograde cholangiopancreatography procedures on 962 patients; 40 patients (12 male, 28 female, with a mean age of 68.1 [SD 4] years) had difficult biliary cannulation and underwent PA-EMR. Technical success was 100%, and none of the patients required a second session. None of the patients had an adverse event, and we encountered no 30-day mortality. The most typical indication was bile duct stones (60%; n = 24), followed by periampullary tumors (15%; n = 6). The total procedure time was 923 (range 392–1224) seconds.PA-EMR was an effective and safe rescue technique in patients with difficult biliary cannulation.